Inventory and assessment of geosites and geodiversity sites of the Ait Attab syncline (M’goun unesco Geopark, Morocco) to stimulate geoconservation, geotourism and sustainable development - Louz, Elhassan; Rais, Jamila; Barakat, Ahmed; Barka, Abdellah Ait; Nadem, Samir (Quaestiones Geographicae, 2023)
The Ait Attab syncline, in the southwestern part of the Moroccan Central High Atlas (CHA), is a vast basin characterised by an exceptional geodiversity illustrating the complete sedimentary series in the CHA. This series offers the opportunity to study regional palaeogeography, transgressive and regressive megasequences, Jurassic-Cretaceous volcanism and Atlas tectonics, and various fossils, including dinosaur footprints. The study area also harbours considerable landscape and cultural wealth that can play a significant role in sustainable geotourism and geoeducation development. To promote and protect this geoheritage wealth, the present work provides the first quantitative and qualitative inventory of geosites of interest by adopting Brilha’s (2016) method. Thus, 3 geotrails covering 8 geosites and 11 geodiversity sites have been selected. The evaluation of these sites confirms their scientific and educational importance, which helps understand the geological, tectonic and palaeogeographical evolution of the Ait Attab syncline. The tourist value of these sites is also high, explained by the high interpretative potential of the geosites and their location as a gateway to the M’Goun Unesco geopark. The degradation risk assessment showed that most of these sites have a medium risk, except for palaeontological and magmatic sites, which have a high degradation risk.